An outbreak of Neospora caninum abortion in a dairy herd from the State of Georgia, United States. Issue 1 (30th August 2020) - Melendez, Pedro; Ilha, Marcia; Woldemeskel, Moges; Graham, Justin; Coarsey, Michele; Baughman, Debi; Whittington, Lisa; Naikare, Hemant
Abstract: An outbreak of 92 abortions out of 1, 700 pregnant cows (5.41%) in a period of 3 weeks (19 May to 05 June 2019) occurred in a Georgia Dairy, USA, in cattle that were between 3 and 7 months of gestation. Two sets of samples (aborted fetuses' organs, placental tissues, aborted cows blood) were submitted for laboratory investigations at the Tifton Veterinary Diagnostic and Investigational Laboratory, College of Veterinary Medicine, University of Georgia (TVDIL, Tifton, GA, USA). An abortion panel testing for the major abortion‐causing agents [e.g. Bovine Viral Diarrhoea Virus (BVDV), Infectious Bovine Rhinotracheitis Virus/ Bovine Herpes Virus‐I (IBR/ BHV‐I), Brucella spp., Leptospira spp .] was conducted on several of the samples. On the first set of samples, microbial cultures, serology and PCR tests for the common abortifacient agents revealed the presence of Neospora caninum (N. caninum) DNA, which was positive by PCR on the placenta and fetal tissues. The second set of diagnostic investigations also identified two out of three submitted freshly aborted fetuses to be positive for N. caninum by PCR and immunohistochemistry. Moreover, all three dams were also sero‐positive for N. caninum . The entire herd was being fed on grass silage harvested from a pasture where feral pigs were hunted previously and carcasses were left behind. As a consequence of this action a large population of wild coyotes were attracted to these carcasses, and likely contaminated the pasture with potential N. caninum ‐infected feces. After the abortion outbreak was resolved, it was recommended that the farmers should avoid disposal of cadavers of hunted animals in the wild, as it could attract carnivorous and omnivorous animals that may potentially spread the disease to the cattle and other wildlife. Abstract : An outbreak of 92 abortions in a period of 3 weeks occurred in a 3, 200 cows Georgia Dairy, USA. Two subset of samples were submitted to the Tifton Veterinary Diagnostic and Investigational Laboratory, University of Georgia. Samples were positive to Neospora caninum by PCR and immunohistochemistry, and dams were positive serologically to the same pathogen.